Systemic immune-inflammation index in critically ill patients with renal failure: a retrospective cohort study from Medical Information Mart for Intensive Care IV (MIMIC-IV) database - Yu-Cheng Chang; Chia-Ying Hsiao; Min-I Su; Ying-Hsiang Lee; Po-Lin Lin; Wei-Ru Chiou; Pi-Yi Chang (BMJ Open)
Objectives Systemic immune-inflammation index (SII) is a biomarker of inflammatory conditions; however, no scoring system has been evaluated for predicting mortality in patients with renal failure in intensive care unit (ICU). This study aimed to determine associations between SII level and mortality in patients with renal failure.Design Using the Medical Information Mart for Intensive Care IV (V.2.0) database (USA), this retrospective study included 837 patients who were admitted to ICU with end-stage renal disease (ESRD), between 2008 and 2019.Primary and secondary outcome measures Cox proportional-hazards models were used to evaluate correlations between SII and outcomes, expressing results as hazard ratios (HRs) with 95% confidence intervals (95% CIs). Regression analysis was used to determine associations between variables and SII.Results In total, 837 adult patients from a total of 76 943 patients admitted to ICU were included, comprising 59.60% males with mean age 62.27±14.9 years and mean BMI 28.36±7.43 Kg/m2. Using median SII (1628 X 109 /L) as cut-off value, high (≥ 1628X109 /L) SII was also associated with an increased risk of ICU mortality (HR 1.97 (95% CI 1.15 to 3.35), p=0.034), in-hospital mortality (HR 1.95 (95% CI 1.23 to 3.09), p=0.017) and total mortality (HR 1.30 (95% CI 1.07 to 1.58), p=0.024).Conclusions SII may predict mortality in critically ill patients admitted to ICU with ESRD. SII ≥ 1628×109 /L correlates significantly with increased ICU mortality, in-hospital mortality and total mortality.